Screening tests for migraine applied to the population of the Bauru campus of the University of São Paulo: a prevalence study - Tanoue, Aline Donata; Honório, Heitor Marques; Conti, Paulo Cesar Rodrigues; Fernandes, Adriano Yacubian (Headache Medicine, 2024)
Introduction: Migraine is a prevalent neurological disorder marked by recurrent and severe headaches that significantly impacts individuals’ quality of life. Objective: This study aims to apply migraine screening tools to the population of the Bauru campus of the University of São Paulo (USP) to estimate the prevalence of migraine and assess the impact of pain on daily life. Methods: A cross-sectional study involved 216 participants, comprising students, faculty, and staff, who completed online questionnaires, including the “ID Migraine,” “International Headache Society Migraine Diagnosis,” and “Migraine Screen Questionnaire.” The impact of migraine on daily activities was assessed using the “Headache Impact Test. The data were analyzed using the Shapiro-Wilk test, Student’s t-test, Mann-Whitney test, and Pearson’s correlation, adopting a 5% significance level. Results: Out of 216 respondents, 69 (31.94%) were diagnosed with migraine using the ID Migraine tool. The International Headache Society questionnaire identified 86 participants (39.81%) as having migraine, while the Migraine Screen Questionnaire indicated 94 participants (43.52%). A combined analysis identified 20.83% of participants (n=45) as having migraine across all questionnaires. A total of 113 participants (52.31%) tested positive for migraine in at least one questionnaire. Results also revealed a strong correlation between positive migraine diagnosis and significant limitations in daily activities, as assessed by the Headache Impact Test (p<0.001). Conclusion: Using multiple migraine screening questionnaires enhances sensitivity and specificity in identifying individuals with migraine. The findings reveal a substantial population at the USP campus likely affected by migraines, emphasizing the need for further research and intervention strategies.